MATA KULIAH KEWIRAUSAHAAN DAN TEKNOLOGI INFORMASI BERPENGARUH TERHADAP MINAT BERWIRAUSAHA MAHASISWA - Syaeful Bakhri; Achmad Otong Busthomi; Gofar Maulana Sidik (IAIN Syekh Nurjati Cirebon, 2022)
Factors that influence students' interest in entrepreneurship in this study are entrepreneurship courses and the use of information technology. The purpose of this research is to find out how the interest of students of the Faculty of Sharia and Islamic Economics IAIN Syekh Nurjati Cirebon to start their own business is influenced by entrepreneurship courses and the use of technology. The research method used is quantitative research with the subject of FSEI IAIN Syekh Nurjati Cirebon students. The research population used the Slovin formula with an error rate of 5%, where as many as 355 students were the sample in this study. This Study’s research aids for descriptive analysis methods and multiple linear regression in this study used SPSS version 22 software. The results showed that entrepreneurship courses and the use of information technology simultaneously affected students' entrepreneurship interests. Analysis of research data shows that the t-test results show that the variables of entrepreneurship courses and the use of information technology partially affect the variable of student interest in entrepreneurship.Keywords: Entrepreneurship; Information Technology; Interest